2019
DOI: 10.3906/bot-1810-1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure and diversity of Adonis L. (Ranunculaceae) populations collected from Turkey by inter-primer binding site (iPBS) retrotransposon markers

Abstract: The genus Adonis L. is a member of Ranunculaceae and consists of perennial and annual herbaceous plants included in the tribe Adonideae under the subfamily Ranunculoideae. Botanically, Ranunculaceae comprises vital medicinal plants. Molecular markers are one of the most effective tools for exploring genetic variation that can enhance breeding efficiency. To identify the genetic diversity of 62 Adonis ecotypes collected from different regions in Turkey, the interprimer binding site (iPBS) retrotransposon system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 37 publications
(71 reference statements)
0
8
1
Order By: Relevance
“…In this study, the mean PIC value was 0.361 which varied 0.163-0.585. Mean PIC value obtained in this study was found much greater than reported by earlier studies using iPBS-retrotransposons markers [25,49].…”
Section: Polymorphism In Turkish Laurel Germplasm Revealed By Ipb-retcontrasting
confidence: 85%
See 1 more Smart Citation
“…In this study, the mean PIC value was 0.361 which varied 0.163-0.585. Mean PIC value obtained in this study was found much greater than reported by earlier studies using iPBS-retrotransposons markers [25,49].…”
Section: Polymorphism In Turkish Laurel Germplasm Revealed By Ipb-retcontrasting
confidence: 85%
“…Analysis of molecular variance (AMOVA) revealed the existence of higher variations within the laurel genotypes and the percentage of the total variance was 85% (Table 4). Pour et al [49] stated that higher variations within genotypes might be due to selection, adaptation, gene flow, genetic drift, variation in ecotypes and the pollination method. Moreover, human activities and environmental fluctuations over time might be responsible for higher variations [55].…”
Section: Genetic Diversity and Population Evaluation For Turkish Laurmentioning
confidence: 99%
“…PCR Amplification was performed in a thermos cycler (SensoQuest Labcycler, Göttingen, Germany) and was conducted in 10 µL reaction mixture comprising 25 ng template DNA, 0.5 U Taq polymerase, 0.25 mM dNTP, 1 µM (20 pmol) primer, 10X buffer; 2 mM MgCl 2 . The PCR thermal cycling profile was as follows: initial denaturation for 3 min at 95 °C, 38 cycles of 95 °C for 60 s, 53–66 °C (annealing temperature depending on primers; for details see Table 2 ) for 60 s, 72 °C for 120 s, and final extension at 72 °C for 10 min [ 22 ]. At 200 V for 105 min, all PCR amplification products were separated by polyacrylamide Mega-Gel dual vertical electrophoresis (Model C-DASG-400-50).…”
Section: Methodsmentioning
confidence: 99%
“…PCR Amplification was performed in a thermos cycler (SensoQuest Labcycler) and were conducted in 10 µL reaction mixture comprising 25 ng template DNA, 0.5 U Taq polymerase, 0.25 mM dNTP, 1 µM (20 pmol) primer, 1X buffer; 2 mM MgCl2. The PCR thermal cycling profile is as follow; initial denaturation for 3 min at 95 • C, 38 cycles of 95 • C for 60 s, 50-60 • C for 60 s, 72 • C for 120 s and final extension at 72 • C for 10 min [29]. All PCR amplification products were resolved in agarose gel at 3% concentration at 200 V for 105 min.…”
Section: Pcr and Ipbs Marker Analysesmentioning
confidence: 99%